2020
DOI: 10.1111/1759-7714.13333
|View full text |Cite
|
Sign up to set email alerts
|

Different administration routes of recombinant human endostatin combined with concurrent chemoradiotherapy might lead to different efficacy and safety profile in unresectable stage III non‐small cell lung cancer: Updated follow‐up results from two phase II trials

Abstract: Background There are two main choices of administration route of recombinant human endostatin (Endostar) available and the treatment options of concurrent chemoradiotherapy (CCRT) have changed over time. The aim of this study was to observe the long‐term efficacy and safety of different administration routes of Endostar combined with CCRT. Methods Patients with unresectable stage III non‐small cell lung cancer (NSCLC) from two phase II trials were included as two cohorts. Both were treated with Endostar combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The use of an infusion pump improved the adherence of patients to rh-endostain treatment. The short-term efficacy and tolerance of Rh-endostain using the above treatment regimen with concurrent radiochemotherapy in unresectable stage Ⅲ NSCLC were satisfactory[ 24 ]. Rh-endostain administered by continuous intravenous infusion using an infusion pump plus concurrent radiochemotherapy was associated with a low incidence of AEs in advanced NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an infusion pump improved the adherence of patients to rh-endostain treatment. The short-term efficacy and tolerance of Rh-endostain using the above treatment regimen with concurrent radiochemotherapy in unresectable stage Ⅲ NSCLC were satisfactory[ 24 ]. Rh-endostain administered by continuous intravenous infusion using an infusion pump plus concurrent radiochemotherapy was associated with a low incidence of AEs in advanced NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the safety was tolerable, this strategy did not prolong survival compared with radiotherapy combined with immunotherapy [ 23 ]. Ma et al reported that continuous intravenous infusion of antiangiogenic drugs can significantly improve DFS and OS in patients with unresectable III stage NSCLC compared with intravenous administration of antiangiogenic drugs [ 24 ]. Therefore, the efficacy of antiangiogenic therapy combined with CCRT in patients with unresectable III stage NSCLC based on high RGD PET uptake is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that endostatin levels in fibrosis cannot effectively reduce fibrosis, suggesting a “blunted” anti-fibrotic response. Full-length recombinant endostatin, with or without an amino-terminal nonamer, has been studied in the clinical setting for anti-angiogenic properties against various cancers, including gastric, nasopharyngeal, glioblastoma multiforme, lung–brain metastases, and two different lung cancers [ 47 , 48 , 49 , 50 , 51 , 52 ]. Endostatin has also ameliorated bleomycin-induced fibrosis in rats, CCl 4 -induced liver fibrosis in mice, hypertrophic scar formation in rabbit ears, and renal injury in streptozotocin diabetic rats [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%